2019
DOI: 10.1101/629618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Androgen-regulated transcription ofESRP2drives alternative splicing patterns in prostate cancer

Abstract: Prostate is the most frequent cancer in men. Prostate cancer progression is driven by androgen steroid hormones, and delayed by androgen deprivation therapy (ADT).Androgens control transcription by stimulating androgen receptor (AR) activity, yet also control pre-mRNA splicing through less clear mechanisms. Here we find androgens regulate splicing through AR-mediated transcriptional control of the epithelial-specific splicing regulator ESRP2. Both ESRP2 and its close paralog ESRP1 are highly expressed in prima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The splicing factor is responsible for the splicing process. Alternative splicing induced by abnormal expression and/or mutations of splicing factors is an important molecular feature of tumorigenesis [12][13][14][15]. The abnormal expression of splicing factors can induce changes in many key tumor-related genes, such as RON, BIN1, S6K1, MNK2, BIM, and BCL-x, which in turn affects malignant phenotypes including cell proliferation, metastasis, chemoresistance, and other processes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The splicing factor is responsible for the splicing process. Alternative splicing induced by abnormal expression and/or mutations of splicing factors is an important molecular feature of tumorigenesis [12][13][14][15]. The abnormal expression of splicing factors can induce changes in many key tumor-related genes, such as RON, BIN1, S6K1, MNK2, BIM, and BCL-x, which in turn affects malignant phenotypes including cell proliferation, metastasis, chemoresistance, and other processes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that ESRP1 , though an ESRP2 paralogue, is not hypermethylated in WTs (figure 2B, C), suggesting that ESRP1 and ESRP2 may have different biological functions and are regulated differently in some instances. Similarly, a recent paper (68) has reported that only ESRP2 and not ESRP1 is regulated by androgens, with important implications in prostate cancer progression.…”
Section: Discussionmentioning
confidence: 85%
“…Splicing alterations are frequent in human cancers (69), including changes induced by ESRP genes, such as in breast cancer (54, 70), prostate cancer (68, 71), renal cell carcinoma (72) and colorectal cancer (73). In most cases, ESRP genes appear to have tumour suppressive properties, presumably because loss of ESRP expression permits EMT (27, 39), which is important in many stages of carcinogenesis, especially the acquisition of malignant characteristics i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation